Effectiveness of an automated billing management system for invoice generation in a logistics company - Eliza Viandrayani Aziz; Tengku Ine Hendriana; Ade Oki Pebiansyah; Rini Ratnaningsih; Savira Putri Calista (Trigin Publisher, 2026)
Efficient revenue management is crucial for PT Jalur Nugraha Ekakurir (JNE) amidst surging delivery volumes. To optimize billing and reduce manual errors from the legacy MyOrion system, JNE migrated to the RAISE Billing Management System. However, implementation faces operational constraints including synchronization gaps requiring manual reconciliation, lengthy maintenance downtimes, and rigid administrative validations that hinder cash flow. This study evaluates RAISE's operational effectiveness at JNE Gedebage's Revenue Assurance unit, mapping billing procedures, identifying systemic bottlenecks, and formulating strategic solutions. Utilizing a Qualitative Descriptive approach, data was gathered through interviews with four purposively selected informants and triangulated with observations, document analysis, and literature reviews. Findings reveal that RAISE significantly optimizes workflows via 24-hour automated synchronization, accelerating high-volume processing, reducing human error, and offering billing flexibility. Despite an 8.7 staff rating, technical barriers like early-month maintenance disrupting peak cycles, filter failures on cash transactions, and reliance on external communication for troubleshooting prevent maximum efficiency. Conclusively, while RAISE enhances speed and accuracy, technical instability limits its potential. Strategic recommendations include shifting maintenance to off-peak mid-month periods, mandating tax ID validation during onboarding, refining cash transaction filters, and developing real-time reconciliation dashboards. Future research should quantitatively measure workflow efficiency, evaluate user satisfaction, explore predictive error-detection analytics, and assess the macroeconomic impacts of technical billing inefficiencies.